Monitoring valve activity in M.edulis and M.galloprovincialis: Valve signal processing ... - Bourdon Lucie (Zenodo, 2023)
This repository provides access to the metadata and scripts used to monitor valve gaping activity of bivalves using valvometry (Valve-Trek Technosmart Europe srl, www.technosmart.eu). The dataset contains valve activity records in csv format per individual sampled from February to May 2023 at Agon-Coutainville (Normandy, France), as well as r scripts for processing, formatting and analyzing valve gaping data. ... : {"references": ["Retailleau, Elie, et al. \"The nocturnal life of the great scallops (Pecten maximus, L.): First description of their natural daily valve opening cycle.\" Plos one 18.1 (2023): e0279690.", "Ahmed, Hafiz, et al. \"Automatic spawning detection in oysters: a fault detection approach.\" 2015 European Control Conference (ECC). IEEE, 2015.", "Bernard, I., et al. \"In situ spawning in a marine broadcast spawner, the Pacific oyster Crassostrea gigas: Timing and environmental triggers.\" Limnology and Oceanography 61.2 (2016): 635-647."]} ...